Alterações ambientais em Parelhas, Rio Grande do Norte: metais pesados em sedimentos de drenagens e percepção de comunidades rurais em relação a mudanças na paisagem - Araújo, Jane Azevedo de (2012)
The conservation of natural resources is essential and constitutes the main subject of many researches, which characterize important aspects concerning the environmental alterations in the ground, water, landscape and socioeconomic information. This study aimed to investigate the anthropogenic input of heavy metals in the environment, in the area of the Parelhas dump site and in part of the Seridó River and to determine the concentration of heavy metals in the sediments. This can result in risk to the environment and human health. In addition, we sought to establish the socioeconomic profile of rural communities adjacent to Seridó River and to comprehend the perception of these dwellers about the changes in the places they live. The area of this study is located in the city of Parelhas/RN, in the centralsouthern part of the State, in the micro-region of the Oriental Seridó. This area comprehends the place where the dump site is located, next to RN 086, the Caldeirão dam, the Quintos river called by local citizens Caldeirão creek and part of Seridó river, perpetuated by the Boqueirão dam, which crosses the city and it includes the rural communities of Almas, Domingas, Sussuarana II and Colonos. Regarding the study with bottom sediments, the samples were collected and taken to the laboratory of geochemistry, where they were dried, sieved, weighted and submitted to weak acid attack. The analysis of heavy metals was held by Atomic Absorption Spectrophotometer - Flame AAS. We applied 23 closed questionnaires constituted by 38 questions to collect informations in the rural communities, oriented to establish the socioeconomic profile and the environmental perception of the participants. The participants were distributed in the communities of Almas (1), Domingas (2), Sussuarana II (10) and Colonos (10). Most of them presented similar socioeconomic profiles. They are from 45 to 60 years old and live in these localities for 20 to 30 years or more. The families are composed by 3 or 4 people; the agriculture is the main activity, livestock is the secondary and 48% of them earn the minimal wage. Regarding the environmental perception, the participants can realize some changes in vegetation, soil, water and landscape. People living longer in the community, and with more years of experience on the local reality can perceive the depletion of the soil, pastures and changes in the landscape. These changes portray how the place was previously and what it represents today. The perception of these changes, besides the environmental ones, includes others concerning the increasing number of dwellers in the last years, as well as the number of houses. The changes happened through activities developed by the dwellers over the years, including agricultural practices, livestock, grass planting and even the cultivation of cotton. The study provided the acquisition of new data about the environmental reality of this region. It can subsidize the definition of public policies that can be implemented from the perspective of conservation of water resources and of the coexistence and survival of man in the semi-arid